Pragmatic Philanthropy Asian Charity Explained - Shapiro, Ruth A. (Springer Nature, 2018)
Asian Philanthropy and Charitable Organizations; Social Investment in Asia; Social Delivery Organizations; Relationships and Philanthropy in Asia; Ultra-high Net-worth Individuals in Asia; How Social Investment Works in Asia; Impact of Charitable Giving in Asia; Relationship with Elites and Social Investment in Asia